2011
DOI: 10.1002/jcop.20492
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems and coping styles of urban and rural high school students in China

Abstract: Few studies have compared urban and rural adolescents' mental health problems, especially in developing countries. The purpose of this study was to investigate the mental health problems and coping styles of adolescents in urban and rural areas in China. A total of 927 urban and rural high school students in Shandong Province of China were recruited for the study. The results of the study are as follows: (a) students in rural low‐socioeconomic status (SES) areas, especially females, had more mental health prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
3
18
1
1
Order By: Relevance
“…7 According to study done by Elgaret et al on one hundred adolescents from an urban junior high school and 146 adolescents from four rural all-grade schools of Canada and Newfoundland province of Canada respectively, rural participants showed better problem focused coping, emotion focused coping and avoidance focused coping however in our study there was no significant difference in urban and rural study participants with regards to problem focused coping, emotion focused coping and avoidance focused coping. 8 According to the study done by Srivastavaet al among the rural and urban school participants in Uttar Pradesh India results showed that urban adolescents use more coping strategies than rural adolescents which used Srivastava Coping Strategies scale and the reason cited behind this is that urban adolescents have many options to solve the problem or cope with stress, but rural adolescents have little amount of option to cope with stress.…”
Section: Discussioncontrasting
confidence: 53%
“…7 According to study done by Elgaret et al on one hundred adolescents from an urban junior high school and 146 adolescents from four rural all-grade schools of Canada and Newfoundland province of Canada respectively, rural participants showed better problem focused coping, emotion focused coping and avoidance focused coping however in our study there was no significant difference in urban and rural study participants with regards to problem focused coping, emotion focused coping and avoidance focused coping. 8 According to the study done by Srivastavaet al among the rural and urban school participants in Uttar Pradesh India results showed that urban adolescents use more coping strategies than rural adolescents which used Srivastava Coping Strategies scale and the reason cited behind this is that urban adolescents have many options to solve the problem or cope with stress, but rural adolescents have little amount of option to cope with stress.…”
Section: Discussioncontrasting
confidence: 53%
“…In response to the outbreak, the Chinese government has taken numerous measures to prevent the spread of viruses (Wang et al, 2020). Although the measures are imperative and effective, the prolonged closure of school, home confinement, restriction of movement and more obesogenic behaviors might have an adverse influence on adolescents (Tandon, 2020a, b), and rural adolescents who are more susceptible to mental health problems (Zhang et al, 2011) might suffer more under these circumstances. Although several studies regarding the psychological impact of COVID-19 have been conducted, evidence regarding the impact of COVID-19 on senior high school students in rural areas is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Ancak alanyazında, daha önce yardım alma/almama değişkeninin anlamlı bir farklılık oluşturduğunu gösteren çalışmalar da bulunmaktadır (Erkan, Özbay, Cihangir-Çankaya ve Terzi, 2012;Meydan ve Lüleci, 2013;Özdemir, 2012). Psikolojik yardım aramaya gönüllülüğün, sınıf düzeyine göre anlamlı bir farklılık göstermediği bulgusu ise alanyazındaki çalışmalara benzerdir (Atıcı, 2008;Kırımlı, 2007;Soykatırcı, 2004 Akkoç, 2013;Aşkın vd., 1995;Düzgün, 1995;Gülgez, 2007;Kelleci, Güler, Sezer ve Gölbaşı, 2009;Kılıç, 1987;Riggio ve Kwong, 2011;Satılmış, 2012;Sakarya, 2013;Yılmaz, 2010;Zhang vd, 2011). Araştırma bulguları kapsamında, obsesif-kompulsif ve paranoid düşünce belirtileri gösteren lise öğrencierinin psikolojik yardım aramaya gönüllülük düzeylerinin daha fazla olduğu belirlenmiştir.…”
Section: Sonuç Ve öNeri̇lerunclassified